Management by Missions Connecting People to Strategy through Purpose - Cardona, Pablo (Springer Nature, 2022)
​A few decades ago, management thinking started to embrace the idea of purpose. The first edition of this book marked an important step in this trajectory; it drew attention to the need for managers to relate the concepts of 'purpose' and 'missions' to strategy, culture and leadership. In the years since, purpose and missions have become business imperatives - not only in terms of remaining competitive but as core in the attempts to have a sustainable impact on the world. The second edition of Management by Missions is an open access book based on substantially more research carried out over fifteen years, involving more than 200 organizations around the world. All of this research supports that the practical models and ideas offered in the book have been tried and tested and actually work in practice. With case studies, anecdote and new research findings, the authors present the main tools of the MBM method (shared missions, missions scorecards, interdependency matrix, missions-based objectives and integral assessment) and the type of leadership needed to implement it. The ideas presented in this book mark a path towards a new management methodology for the XXI century and a new way of understanding the work that managers do.